ANALYSIS OF DISEASE SEVERITY ON CITRUS LEAVES (CITRUS spp.) USING IMAGEJ AND PLANTIX SOFTWARE - Hasanah, Melly Rya; Rosadi, Imam; Oktavianingsih, Linda; Fitriani, Nur Indah; Fera, Okta; Addin, Rosita; Ayuni, Cici Lis Qurrotun; Muhammadiyah, Muhammadiyah (Universitas Tanjungpura, 2023)
The purpose of this case study is to determine the severity of citrus leaves using Plantix software and ImageJ software. Based on the results of this case study, it was found that the severity of the disease using ImageJ software was on citrus leaves at the first location (10.641%), citrus leaves at the second location (53.278%), and citrus leaves at the third location (15.828%) which were generally the fruit plants caused by fungi and based on the results of Plantix software data, diseases in the first, second, and third locations of citrus leaves were caused by bacterial diseases. Based on the results of bacterial cell culture, isolates were found to be round white in color with a slight yellowness which is a characteristic of Xanthomonas axonopodis bacteria with a large number of ±12 colonies and a smaller number of ±35 colonies. Using software and imageJ can help farmers to find out the types of pests that attack citrus plants so that farmers can handle plants to minimize damage to citrus plants caused by pests.